(untitled) (Global Journal of Science Frontier Research, 2014)
On farm studies were conducted to determine the effects of intercrop row arrangements on the performances of maize (Zea mays L.) and haricot bean (Phaseolus vulgaris L.) crops and the residual soil at Hallabaand Tabaareas, southern Ethiopia. The result revealed that there were significant differences among the cropping patterns on growth and yield components of both crops. Grain yield of the maize crop was observed to be the highest insole stand, which was statistically at par with the maize grown in 1:1 ratio with haricot bean. There was 15.5% yield reduction in maize when the number of haricot bean rows introduced between two maize rows increased from one to three, attributable to aggravation of interspecific competition in the latter case. In the case of haricot bean crop, compared to the sole stand intercropping of one, two and three rows of haricot bean between two rows of maize had resulted in yield reductions of 56, 44.5 and 28.2%, respectively. Evaluation of the land use efficiency of the system in terms of land equivalent ratio (LER) has, however, showed improvement across the cropping pattern, where by 1:3 maize-haricot bean row ratio gave the highest land use efficiency value, 54% more efficient than growing both crops in sole stand. Total N content of the residual soil has also showed significant improvement due to the introduction of the leguminous haricot bean into the cropping system. In contrast, sole maze stands had contributed the least in amending the acidity problem of the experimental soils.